Developing professional competencies in pre-service philology teachers through pedagogical practicum - Шовковий, В’ячеслав Миколайович; Шовкова, Тетяна Анатоліївна (Київський національний університет імені Тараса Шевченка, 2025)
Background. Developing professional competencies is a crucial aspect of the educational training of preservice philology teachers, particularly during their pedagogical practicum. As future educators, they must acquire a broad range of competencies to perform their roles effectively within the school environment. The professional standard 'Teacher of General Secondary Education Institution' outlines the essential competencies, which encompass linguistic-communicative, subject-methodological, informational-digital, psychological, emotional-ethical, inclusive, health-promoting, prognostic, organisational, evaluative-analytical, and pedagogical partnership competencies, as well as the capacity for lifelong learning. The purpose of the article is to outline the types of activities that student interns (future philology teachers) can perform during their pedagogical practicum and which are aimed at their acquisition of competencies stipulated by the professional standard "Teacher of a general secondary education institution". Results and discussion. The article examines the development of a number of competencies (linguistic and communicative, disciplinary, informational and digital, psychological, emotional and ethical competence, inclusive, health-preserving, prognostic, organisational, evaluative and analytical competences, as well as pedagogical partnership competence and the ability to learn throughout life) through various practical activities during pedagogical practice. These activities are designed to help student-interns acquire and improve the knowledge and skills outlined in the professional standard. The article examines in detail specific activities and measures that students can use to achieve high academic results, such as conducting lessons, organising extracurricular activities, participating in research and pedagogical projects, analysing legislative acts and curricula, and utilising digital technologies. In conclusion, the study demonstrates that the professional competencies of future teachers are not only built through theoretical training, but also through active, practical activities that contribute to their development and improvement.

Статтю присвячено формуванню професійних компетентностей майбутніх учителів-філологів у процесі педагогічної практики, зокрема визначенню видів діяльності, які студенти-практиканти (майбутні вчителі-філологи) можуть виконувати під час проходження педагогічної практики та які спрямовані на набуття ними компетентностей, передбачених професійним стандартом "Вчитель закладу загальної середньої освіти". Відповідно до професійного стандарту освітній процес вимагає від педагога розвитку множинних компетентностей, які сприяють успішному виконанню його функцій в школі. У статті детально розглянуто шляхи набуття низки компетентностей (мовно-комунікативної, предметно-методичної, інформаційно-цифрової, психологічної, емоційно-етичної компетентності, інклюзивної, здоров'язбережувальної, прогностичної, організаційної, оцінювальноаналітичної компетентності, а також компетентності педагогічного партнерства та здатності до навчання протягом усього життя) через практичну діяльність майбутніх учителів. Кожна компетентність описана через конкретні види діяльності та заходи, які студенти можуть виконувати під час педагогічної практики для досягнення високих результатів у навчанні. Процес набуття компетентностей передбачає проведення уроків, позаурочних заходів, участь у науково-педагогічних проєктах, аналіз законодавчих актів та навчальних програм, а також використання цифрових технологій. У підсумку, дослідження доводить, що професійні компетентності майбутнього вчителя не тільки забезпечуються теоретичною підготовкою, але й є наслідком активної практичної діяльності, що сприяє їх формуванню і вдосконаленню.
Формування професійних компетентностей майбутніх учителів-філологів у процесі педагогічної практики
Keywords: педагогічна практика; професійний стандарт "Вчитель закладу загальної середньої освіти"; види діяльності; професійні компетентності вчителя-філолога; pedagogical practicum; professional standard "Teacher of General Secondary Education Institution"; types of activities; professional competencies of a philology teacher